1999
DOI: 10.1002/1529-0131(199907)42:7<1481::aid-anr23>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Distinct vascular patterns of early synovitis in psoriatic, reactive, and rheumatoid arthritis

Abstract: The distinct vascular patterns in PsA and ReA compared with those in RA may reflect different specific vascular factors in the pathogenesis of these arthritides. Vascularity and villous hypertrophy are the most reliable features of synovitis grading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(116 citation statements)
references
References 15 publications
6
101
1
5
Order By: Relevance
“…Whereas several groups of investigators previously identified diseaserelated synovial parameters in well-defined patients with full-blown and well-established disease (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), the present study globally confirms these findings in an independent cohort of 67 patients fulfilling classification criteria.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Whereas several groups of investigators previously identified diseaserelated synovial parameters in well-defined patients with full-blown and well-established disease (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), the present study globally confirms these findings in an independent cohort of 67 patients fulfilling classification criteria.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, less specific synovial features probably lack direct diagnostic value when used as single parameters, but such features might be combined in multiparameter models to increase the predictive value in an individual patient. Such markers include the pattern and degree of vascularity, lining layer hyperplasia, and infiltration by T and B cells, as well as the presence of lymphoid aggregates, polymorphonuclear cells, and dendritic cells (21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…W ŁZS zwracały uwagę wyraźne zmiany naczyniowe. Polegały one na występowaniu liczniejszych niż w RZS drobnych naczyń krwionośnych, o szerokim świetle i charakterystycznie poskręcanych ścianach [19]. W odróżnieniu od RZS w naciekach zapalnych występowały granulocyty obojętnochłonne i większa liczba makrofagów z ekspresją CD163 [20].…”
Section: A Comparison Of Histopathological Changes In the Synovial Meunclassified
“…The psoriatic synovium is characterized by increased vascularity which is considered an early feature of PsA [19,20]. The presence of dilated and tortuous vessels denotes impaired angiogenic mechanisms which are responsible for the construction of this abnormal vascular net.…”
Section: Immunopathologymentioning
confidence: 99%
“…The interplay of activating and inhibitory Ig-like receptors could cause an alteration of the functional status of NK cells which subsequently could augment the inflammatory response. Another early histological feature of psoriatic synovium is the increased vascularity and the presence of tortuous and dilated vessels [19,20]. This abnormal vascular net is probably attributed to impaired angiogenic underlying mechanisms which involve many angiogenic factors such as vascular endothelial growth factor (VEGF), transforming growth factor (TGFβ) and angiopoietins.…”
Section: Overview and Conclusionmentioning
confidence: 99%